2018
DOI: 10.3389/fpsyg.2018.02268
|View full text |Cite
|
Sign up to set email alerts
|

Are Proselfs More Deceptive and Hypocritical? Social Image Concerns in Appearing Fair

Abstract: Deception varies across individuals and social contexts. The present research explored how individual difference measured by social value orientations, and situations, affect deception in moral hypocrisy. In two experiments, participants made allocations between themselves and recipients with an opportunity to deceive recipients where recipients cannot reject their allocations. Experiment 1 demonstrated that proselfs were more deceptive and hypocritical than prosocials by lying to be apparently fair, especiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…By investigating MH at the interpersonal level, Lönnqvist et al (2014) deduced that MH is the process of impression management or self-deception. Hypocritical people not only adopt self-interest behavior but also desire to maintain a virtuous moral image (Caviola and Faulmüller, 2014;Lönnqvist et al, 2014;Chance et al, 2015;Tang et al, 2018). Two types of explanations have been provided for hypocrisy: social preference explanations (Fehr and Schmidt, 1999) and social signaling explanations (Barden et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…By investigating MH at the interpersonal level, Lönnqvist et al (2014) deduced that MH is the process of impression management or self-deception. Hypocritical people not only adopt self-interest behavior but also desire to maintain a virtuous moral image (Caviola and Faulmüller, 2014;Lönnqvist et al, 2014;Chance et al, 2015;Tang et al, 2018). Two types of explanations have been provided for hypocrisy: social preference explanations (Fehr and Schmidt, 1999) and social signaling explanations (Barden et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that it is difficult for real feedback to reduce self-deception to the level of the control group after repeated feedback (Chance et al, 2015; Tang et al, 2018). However, our research found that one incident of negative feedback decreased self-deception to the level of the control group.…”
Section: Discussionmentioning
confidence: 95%
“…Self-deception reduces the cognitive dissonance caused by unethical behavior (Lauria et al, 2016). Self-deception is regard as a strategy to deal with conflict between self-interest and moral standards (Batson et al, 1999; Tang et al, 2017, 2018). Even if unconsciously one thinks of it as a kind of immoral behavior, the conscious mind rationalizes this immoral behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The GFP, as a higher‐order trait of these five lower‐order personality traits (Musek, 2007), has also been shown to be positively associated with integrity (Van der Linden et al, 2014). As being deceptive and self‐interested are typical characteristics of moral hypocrisy (Monin & Merritt, 2012; Tang et al, 2018; Weiss & Burgmer, 2021), individuals with lower GFP scores may exhibit higher levels of moral hypocrisy than those with higher scores. Additionally, previous studies have found that the GFP is positively associated with self‐esteem (Pelt et al, 2020) and self‐concept (Rodriguez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%